2015
DOI: 10.1016/j.ecoenv.2015.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute NH3 air pollution on N-sensitive and N-tolerant lichen species

Abstract: Lichens are sensitive to the presence of ammonia (NH3) in the environment. However, in order to use them as reliable indicators in biomonitoring studies, it is necessary to establish unequivocally the occurrence of certain symptoms following the exposure to NH3 in the environment. In this paper, we simulated an episode of acute air pollution due to the release of NH3. The biological effects of acute air pollution by atmospheric NH3 have been investigated using N-sensitive (Flavoparmelia caperata) and N-toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Lichen functional groups, defined as groups of species with a similar response to specific environmental factors (Lavorel et al, 2002), are widely used as a monitoring tool (e.g. Benítez et al, 2018;Paoli et al, 2015). The attribution of a species to a certain functional group usually reflects an expert-assessment based on data available in the literature (for ex.…”
Section: Introductionmentioning
confidence: 99%
“…Lichen functional groups, defined as groups of species with a similar response to specific environmental factors (Lavorel et al, 2002), are widely used as a monitoring tool (e.g. Benítez et al, 2018;Paoli et al, 2015). The attribution of a species to a certain functional group usually reflects an expert-assessment based on data available in the literature (for ex.…”
Section: Introductionmentioning
confidence: 99%
“…The main sources of nitrogen in the agricultural landscape are ammonia (NH 3 ) and the ammonium cation (NH 4 + ). Agricultural activities, principally livestock farming, the application of organic and mineral fertilizers, and biomass burning, contribute significantly to emissions of these compounds [5][6][7][8][9][10][11][12].…”
Section: Nitrogen Pollution In the Agricultural Landscapementioning
confidence: 99%
“…Those authors demonstrated the sensitivity of photosystem II to this N pollutant; a marked decrease in the potential quantum yield of PSII was detected in thalli exposed near a sheep farm [9]. The sensitivity of the photobiont in Flavoparmelia caperata to N pollution was manifested by chlorophyll degradation and diminished photosynthetic performance, whereas in Xanthoria parietina, only the highest concentration affected the autotroph [10]. Under the impact of ammonium nitrate (NH 4 NO 3 ), the photobiont of Cladonia arbuscula ssp.…”
Section: Physiological and Biont Responses Of Lichens To Nitrogen Inputmentioning
confidence: 99%
“…Depending on the species ( Johansson et al 2011 , Paoli et al 2015 ) and certain climate factors, the acidification of pigments from increasing N deposition (in the form of NH 4 + , NO 3 − , and organic N) can harm lichens’ photosynthetic abilities and therefore their ability to capture energy and C ( Fig. 1 ).…”
Section: Echanism Of E Ffect From a Tmospheric D Eposition On L mentioning
confidence: 99%